'It's more than just mentoring': critical mentoring Black and Latino males from college to the community. Issue 2 (4th March 2021) - Brooms, Derrick R.; Franklin, William; Clark, Jelisa S.; Smith, Matthew
ABSTRACT: This qualitative study investigated the engagement and leadership experiences of 12 Black and Latino male college students at a Hispanic-serving institution. Specifically, we explore how these students understood and made meaning of their experiences as mentors for local middle school and high school males of color. The students articulated three significant components of their youth mentoring experiences that shaped their leadership: (a) commitment to community; (b) serving as a role model to youth – and among their peers – and (c) using a person-first approach to enrich students holistically, enhance their schooling experiences, and support their academic efforts. The student narratives provide a frame for promoting and supporting engagement for college men of color, reveal the importance of community cultural wealth, and speak to ways to build leadership capital, as these experiences can create and enhance their leadership skills and position them to be community change agents.